TRPA1 mediates mechanical currents in the plasma membrane of mouse sensory neurons. - Daniel Vilceanu; Cheryl L Stucky (PLoS ONE)
Mechanosensitive channels serve as essential sensors for cells to interact with their environment. The identity of mechanosensitive channels that underlie somatosensory touch transduction is still a mystery. One promising mechanotransduction candidate is the Transient Receptor Potential Ankyrin 1 (TRPA1) ion channel. To determine the role of TRPA1 in the generation of mechanically-sensitive currents, we used dorsal root ganglion (DRG) neuron cultures from adult mice and applied rapid focal mechanical stimulation (indentation) to the soma membrane. Small neurons (diameter <27 microm) were studied because TRPA1 is functionally present in these neurons which largely give rise to C-fiber afferents in vivo. Small neurons were classified by isolectin B4 binding. Mechanically-activated inward currents were classified into two subtypes: Slowly Adapting and Transient. First, significantly more IB4 negative neurons (84%) responded to mechanical stimulation than IB4 positive neurons (54%). Second, 89% of Slowly Adapting currents were present in IB4 negative neurons whereas only 11% were found in IB4 positive neurons. Third, Slowly Adapting currents were completely absent in IB4 negative neurons from TRPA1-/- mice. Consistent with this, Slowly Adapting currents were abolished in wild type IB4 negative neurons stimulated in the presence of a TRPA1 antagonist, HC-030031. In addition, the amplitude of Transient mechanically-activated currents in IB4 positive neurons from TRPA1-/- mice was reduced by over 60% compared to TRPA1+/+ controls; however, a similar reduction did not occur in wild-type neurons treated with HC-030031. Transfection of TRPA1 in HEK293 cells did not significantly alter the proportion or magnitude of mechanically-activated currents in HEK293 cells, indicating that TRPA1 alone is not sufficient to confer mechanical sensitivity.These parallel genetic and pharmacological data demonstrate that TRPA1 mediates the Slowly Adapting mechanically-activated currents in small-diameter IB4 negative neurons from adult mice. The TRPA1 protein may also contribute to a complex that mediates Transient mechanically-activated currents in small IB4 positive C fiber type neurons.